Revisiting Mengzi and Xunzi with Aristotle’s “Potentiality-Actuality” as the Analytic Framework - NG, Kai Wen (Journal of Chinese Literature And Culture 馬大華人文學與文化學刊, 2018)
Abstract There is a new surge of investigation which has rendered Aristotle’s thoughts with new interpretations. One of the problems is that which revolving the understanding of the concepts of potentiality and actuality. If we incorporate the new understanding of the concepts with the definition of change, it could provide a critical perspective by interpreting change from the sense of being, i.e., change is not merely about a process in which we move from one end to the other. Mengzi and Xunzi have similar way of argument when it comes to the issue of human nature, but their conflicting stances of good and bad have prevailed against their possible association. The triple scheme of potentiality and actuality have provided a juncture of associating their accounts of human nature.